TITLE EVALUATION OF FACTORS ASSOCIATED WITH THE QUALITY OF BPJS PATIENT REGISTRATION SERVICES AT BARANTI PUBLIC HEALTH CENTER, SIDENRENG RAPPANG REGENCY - Firda Ramadani; Zulkarnain Sulaiman; Sunandar Said; Devy Febrianti (CV. Fahr Publishing, 2026)
This study was motivated by the persistence of problems in BPJS patient registration services, such as long queues, unclear procedures, and suboptimal staff communication. These conditions have the potential to reduce service quality and patient satisfaction. This study aimed to analyze the factors associated with the quality of BPJS patient registration services at Baranti Public Health Center, Sidenreng Rappang Regency. This study used a quantitative approach with a cross-sectional design. The sample consisted of 99 respondents determined using the Slovin formula from a total population of 8,701 patients. Data were collected through Likert-scale questionnaires and observation. Independent variables included facilities and infrastructure, staff attitudes and communication, and service procedures, while the dependent variable was service quality. Data were analyzed using the Chi-Square test. The results showed that facilities and infrastructure had a significant relationship with service quality (p < 0.001), service procedures had a significant relationship with service quality (p < 0.001), and staff attitudes and communication also had a significant relationship with the quality of BPJS patient registration services (p < 0.001). The most dominant factor influencing service quality was staff attitudes and communication. It can be concluded that improving service quality can be achieved through improving facilities, enhancing staff competencies, and simplifying service procedures.